Brazilian Unified Health System Resource management in Bahia, Brazil: an analysis considering the influence of electoral cycles in municipal efficiency index (Gestão & Regionalidade, 2017)
This paper verifies possible variations of efficiency in the management of Brazilian Unified Health System (SUS) resources due to election period in the state of Bahia, in 2008, 2009, 2012, and 2013, which groups election and post-election years. The paper symbolizes the first national attempt to relate efficiency with the interests of policymakers during elections. Data Envelopment Analysis with variable returns and product orientation was the chosen method. We observe that there is no efficiency gain in the election period, but in the post-election period, contradicting the hypothesis that in election year municipal managers seek to efficiently use the resources of SUS.